Symmetrical Short Circuit Parameter Differences of Double Fed Induction Generator and Synchronous Generator Based Wind Turbine - Muhammad Shahzad Nazir; Qinghua Wu; Mengshi Li; Luliang Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Considering the importance of perturbations during short circuit (SC) in power conversion devices, this study designed to find out the efficacy of symmetrical short circuit (SSC) of the synchronous generator (SG) and doubly fed induction generators (DFIG). Both wind power systems were separately built (Park’s model) and simulated. Simulation results showed that the DFIG is more efficient, fault tolerant, and proficient systems as compared to the SG based on the transient time, steady state, maximum current, and voltage dip values. This study can extend to design protection schemes, more accurate, stable and optimal proficient wind power conversion devices.